2007
DOI: 10.1007/s11224-007-9266-7
|View full text |Cite
|
Sign up to set email alerts
|

Structure and hydrogen bonding in polyhydrated complexes of guanine

Abstract: Molecular structure of complexes of guanine with 12, 13, 16, and 17 water molecules were calculated using B3LYP/6-311G(d,p) level of theory. Interaction with water results in some deformation of geometrical parameters of guanine, which can be described as contribution of zwitter-ionic resonant form into the structure of DNA base. Saturation of water binding sites within guanine creates possibilities for the formation of the NÁÁÁH-O hydrogen bond where the nitrogen atom of amino group acts as proton acceptor. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 56 publications
1
36
0
Order By: Relevance
“…However, recent investigation of polyhydrated complexes of adenine [6] and guanine [7] demonstrated the possibility of formation of hydrogen bonds with participation of the nitrogen atom of imidazole and pyrimidine rings possessing intermediate geometrical parameters as compared to the mentioned above. In particular, the values of the C-C-NÁÁÁH torsion angles were in the range 120-150°which are significantly deviated from ideal values of 90°and 180°.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent investigation of polyhydrated complexes of adenine [6] and guanine [7] demonstrated the possibility of formation of hydrogen bonds with participation of the nitrogen atom of imidazole and pyrimidine rings possessing intermediate geometrical parameters as compared to the mentioned above. In particular, the values of the C-C-NÁÁÁH torsion angles were in the range 120-150°which are significantly deviated from ideal values of 90°and 180°.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the values of the C-C-NÁÁÁH torsion angles were in the range 120-150°which are significantly deviated from ideal values of 90°and 180°. An analysis of characteristics of such hydrogen bonds using Natural Bond Orbitals theory revealed that in some cases existing hydrogen bonds cannot be clearly described as O-HÁÁÁN or O-HÁÁÁp because both lone pair of the nitrogen atom and p-system served as proton withdrawal fragments [7]. It was suggested to consider such hydrogen bonds as mixed O-HÁÁÁN/O-HÁÁÁp bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of bases to change their geometries under influence of water environment was demonstrated most clearly in the case of formation of closed chains of water molecules around nucleobases. Recent studies on molecular structure of complexes of uracil and thymine [19] with 11 water molecules, cytosine with 14 water molecules [20], and guanine with 12 water molecules [21] revealed significant polarization of bases. Structure of hydrated molecules cannot be described by canonical chemical formulas due to significant contribution of zwitter-ionic resonant forms into total structure of nucleobases (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…In this article, we present results of investigation of conformational flexibility of hydrated thymine, cytosine, [20,21] that polarization of nucleobases within this model of solvent is smaller when compared to polyhydrated complexes that explicit include water molecules. However, all trends of deformation of molecular structure remain the same for both models of solvation.…”
Section: Introductionmentioning
confidence: 99%
“…The last paper in this issue is a computational study by Sukhanov et al [75] who investigated structure and hydrogen bonding in polyhydrated complexes of guanine using DFT. As revealed, the interaction of guanine with water may cause some polarization of the nucleobase, which can be considered as the contribution of the double zwitterionic resonance form to the total structure of the molecule.…”
mentioning
confidence: 99%